Shear resistance of trapezoidal corrugated web in local buckling - Usman F. (Trans Tech Publications Ltd, 2023)
This paper presents analytical studies using Eigenvalue buckling analysis in the Finite Element Method to determine shear buckling and subsequently determine shear resistance of thin plated member with trapezoidal corrugated web. The result is compared with experimental results. It is found that the proposed equations give good agreement to the experimental results. However, the buckling coefficient k is still not generate a good shear stress based on its slenderness ratio hw/tw. © (2014) Trans Tech Publications, Switzerland.